Characteristics of Chemical Composition of Some Plants - Samadova Nozima Negmat kizi (Zien Journals, 2023)
The chemical composition of plants is very complex and consists of various organic and mineral substances. All of them will not be medicinal and will not have a curative effect in the treatment of diseases. Some of them interfere with the preparation of medicines, cause their quality to deteriorate during the storage of medicinal products, or cause rapid decomposition of the main active chemical compounds. Therefore, substances found in the composition of medicinal plants are divided into three groups from the point of view of medicine and pharmacy
Keywords: chemical compounds; biological active substance; therapeutic value